Effect of Planting Methods on the Growth and Yield of Carrot (Daucus carota L) in Humid Tropical Zone (e-Proceedings of the Faculty of Agriculture International Conference, 2023)
The experiment was conducted at the research farm of the Department of Crop Science and Horticulture, Nnamdi Azikiwe University, Awka, Nigeria; to study the effect of planting methods on the growth and yield of carrot (Daucus carota L). Two planting methods, direct sowing and transplanting were used as treatments for the experiment, which was laid out in a Randomized Complete Block Design (RCBD) and replicated four times. Data was collected on the growth, yield and root marketability. The collected parameters were statistically analyzed by analysis of variance table and means were separated using Least Significance Difference (LSD) at 5 percent level of significance with the GENSTAT 2014 Edition. The results showed no significant variation between the planting methods on the stem girth and leaf number at some dates, while transplanting significantly varied (P
Keywords: Carrot; Treatment; Direct Sowing; Marketability; Plant biomass